We get that when the expression ∛ 54 x³ - ∛ 16 x³ is simplified using subtraction, we get the result as ∛ 2 x.
We are given the expression:
∛ 54 x³ - ∛ 16 x³
We need to subtract to simplify the expression.
First, we know that:
54 = 2 × 3 × 3 × 3
16 = 2 × 2 × 2 × 2
So,
∛ 54 x³ = 3 ∛2 x
∛ 16 x³ = 2 ∛2 x
So, we get the expression as:
3 ∛ 2 x - 2 ∛ 2 x
Combining the like terms, we get that:
= ∛ 2 x
Therefore, we get that when the expression ∛ 54 x³ - ∛ 16 x³ is simplified using subtraction, we get the result as ∛ 2 x.
Learn more about subtraction here:
https://brainly.com/question/25421984
#SPJ4